Persepsi Publik terhadap Citra Platform Hiburan Digital Vindes - Alif Ramadhana; Sidiq Nurhidayat; Muhammad Fathir Rahman; Sadiyah El Adawiyah (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The development of digital communication technology has transformed the media consumption landscape in Indonesia, shifting the dominance of conventional media to internet-based platforms such as YouTube, Instagram, and TikTok. This study aims to analyze public perception of the digital entertainment platform Vindes, founded by Vincent Rompies and Deddy Mahendra Desta. Using a positivism paradigm with a descriptive quantitative method, this study measures two main dimensions of image: functional image (content quality, originality, consistency) and symbolic image (host personality, credibility, cultural values). Data were collected through an online survey of respondents meeting specific content exposure criteria. The research findings indicate that Vindes has successfully built a strong functional image through production quality equivalent to television standards and innovative (out-of-the-box) program concepts. Symbolically, the personas of Vincent and Desta create deep parasocial relationships with the audience, significantly strengthening brand loyalty. There is high alignment between the intended image by platform managers and the perceived image by the public. This study concludes that authenticity and interactivity are key to maintaining reputation in the new media era